Can non‐typeable Haemophilus influenzae carriage surveillance data infer antimicrobial resistance associated with otitis media? - Sophia Bowman‐Derrick; Tegan M. Harris; Jemima Beissbarth; Mariana Kleinecke; Katrina Lawrence; Teresa M. Wozniak; Amy Bleakley; Angela Rumaseb; Michael J. Binks; Robyn L. Marsh; Peter S. Morris; Amanda J. Leach; et al. (Wiley, 2023)
ABSTRACT Importance In remote communities of the Northern Territory, Australia, children experience high rates of otitis media (OM), commonly caused by non‐typeable Haemophilus influenzae (NTHi). Few data exist on antibiotic susceptibility of NTHi from OM. Objective To determine whether population‐level nasopharyngeal NTHi antibiotic susceptibility data could inform antibiotic treatment for OM. Methods NTHi isolates (n = 92) collected from ear discharge between 2003 and 2013 were selected to time‐ and age‐match NTHi isolates from the nasopharyngeal carriage (n = 95). Antimicrobial susceptibility were tested. Phylogenomic trees and a genome‐wide association study (GWAS) were performed to determine the similarity of nasopharyngeal and ear isolates at a population level. Results Among 174 NTHi isolates available for antimicrobial susceptibility testing, 10.3% (18/174) were resistant to ampicillin and 9.2% (16/174) were resistant to trimethoprim‐sulfamethoxazole. Small numbers of isolates (≤3) were resistant to tetracycline, chloramphenicol, or amoxicillin‐clavulanic acid. There was no statistical difference in the proportion of ampicillin‐resistant (P = 0.11) or trimethoprim‐sulfamethoxazole‐resistant isolates (P = 0.70) between ear discharge and nasopharynx‐derived NTHi isolates. Three multi‐drug resistant NTHi isolates were identified. Phylogenomic trees showed no clustering of 187 Haemophilus influenzae isolates based on anatomical niche (nasopharynx or ear discharge), and no genetic variations that distinguished NTHi derived from ear discharge and nasopharyngeal carriage were evident in the GWAS. Interpretation In this population‐level study, nasopharyngeal and ear discharge isolates did not represent distinct microbial populations. These results support tracking of population‐level nasopharyngeal NTHi antibiotic resistance patterns to inform clinical management of OM in this population.